Seismic performance of the replaceable steel links with different short length ratios - Liquan Xiong; Zhengchao Guo; Jun Cai; Kaiyu Jiang; Linyan Li (Scientific Reports)
Abstract Compared with the traditional frame structures, the novel composite frame with replaceable steel links can realize the rapid recovery of building occupancy after seismic actions to provide the capacity of reducing structural damage and ensure the reuse of a structure. In this system, plastic deformation and damage mainly concentrated in the steel links serving as the structural fuses and other structural members still remained elastic or minor plastic, and then the damaged steel links can be easy for replace. In order to study the seismic performance of the replaceable steel links, a total of four test specimens with different short length ratios were designed. A low-cycle reversed loading test was carried out in terms of failure characteristic, hysteretic response and shear strength. The results indicated that all tested specimens presented a stable and full hysteretic response while the steel links especially exhibited a large inelastic deformation capacity and fully developed shear strength as the structural fuses. Besides, failure modes of steel links included two types of shear failure and bending-shear failure, followed by two types of damage features, including web-to-stiffener weld tear, web buckling, flange-to-end plate weld tear and flange buckling, respectively. Finally, nonlinear finite element models (FEMs) of test specimens were implemented by the Abaqus software. The numerical results were in good agreement with the experimental results in terms of load-deformation curves, initial stiffness, the development of Von Mises stress and cumulative plastic equivalent strain (PEEQ) indexes to facilitate design practice.